Frequency of Hepatitis E in Children (Journal of Rashid Latif Medical College, 2022)
Objective: Data obtained through high throughput technologies isincreasing our current understanding of the fact that like the hepatitis viruses, hepatitis E virus (HEV) has been difficult to study because of limitations in cell culture systems and small animal models. The objective of this study was to determine the frequency of hepatitis E virus infection in pediatric patients reporting to a tertiary care hospital. Materials and Methods: Six months (1- 04-08 to 31-10-08) study was conducted at Department of Pediatrics, Services Hospital Lahore. One hundred and sixty patients and sampling technique used was Non probability (Purposive sampling). Both genders were included in the study. Results: Hepatitis E was seen in 20 patients, constituting a total of 12.5% of all the patients. Conclusion: Hepatitis E is a fairly common and under diagnosed cause of acute hepatitis in pediatrics patients and introducing adequate preventive measures can reduce the morbidity.